Microsomal epoxide hydrolase, glutathione S-transferase P1, traffic and childhood asthma. Issue 12 (21st August 2007) - Salam, Muhammad T; Lin, Pi-Chu; Avol, Edward L; Gauderman, W James; Gilliland, Frank D
Abstract : Background: Microsomal epoxide hydrolase (EPHX1) metabolises xenobiotics including polyaromatic hydrocarbons (PAHs). Functional variants at this locus have been associated with respiratory diseases. The effects of EPHX1 variants may depend upon exposures from tobacco smoke and traffic emissions that contain PAHs as well as variants in other enzymes in the PAH metabolic pathway such as glutathione S-transferase (GST) genes. A study was undertaken to investigate associations of variants in EPHX1, GSTM1, GSTP1 and GSTT1 with asthma and the relationships between asthma, EPHX1 metabolic phenotypes and exposure to sources of PAHs. Methods: Odds ratios (ORs) and 95% confidence intervals (CIs) were computed to estimate the associations of genetic variants and exposures with asthma phenotypes using data from 3124 children from the Children's Health Study. Results: High EPHX1 activity was associated with an increased risk for lifetime asthma (OR 1.51, 95% CI 1.14 to 1.98) which varied by GSTP1 Ile105Val genotype and by residential proximity to major roads (p for interaction = 0.006 and 0.03, respectively). Among children with GSTP1 105Val/Val genotype, those who had high EPHX1 phenotype had a fourfold (95% CI 1.97 to 8.16) increased risk of lifetime asthma than children with low/intermediate EPHX1 phenotype. Among children living within 75 metres of a major road, those with high EPHX1 activity had a 3.2-fold (95% CI 1.75 to 6.00) higher lifetime asthma risk than those with low/intermediate activity. The results were similar for current, early persistent and late onset asthma. Children with high EPHX1 phenotype, GSTP1 Val/Val genotype who lived <75 metres from a major road were at the highest asthma risk. Conclusion: EPHX1 and GSTP1 variants contribute to the occurrence of childhood asthma and increase asthma susceptibility to exposures from major roads.